Actividad coagulante de la semilla annona muricata (guanábana) en aguas de la cuenca media del Río Bogotá (2021)
High turbidity concentrations in water bodies are responsible for limiting crop irrigation, which are located in some zones of the country, as in the case of Bogotá, Colombia. There are some methods for the removal of the different suspended particles by adding chemical coagulants (aluminum sulfate, ferric coagulants, among others), which can cause problems to human health and the environment itself.Reason why, some authors have investigated about natural alternatives in order to totally or partially replace inorganic products that are currently used, from fruity seeds and plants. The objective of the current study was to evaluate Annona muricata’s coagulant activity in the middle basin of Bogota river, through the low volumes technique adapted from environmental microbiology group of the Hunglica Tekniska Hogskolan Univerisity’s biotechnology department, located in Stockholm (Sweden). In order to achieve it, we performed an experimental set-up from the water samples obtained from 2 different sampling points, localized “vereda Chorrillos”, Bogota. In order to perform the experimental process, we used dry seeds and after that, we made the tests with 8 different concentrations: 100, 250, 500, 1000, 1500, 2000, 2500 y 3000 ppm. Then, 4 copies for each test with the objective of ensuring better statistical results. The solutions used were: wáter, ethanol and acetic acid, the we used seed’s Shell and embryo. About the organic compounds used, we employed mimosa, castaño and quebracho. On the other hand, sulfate was used as a control. The results obtained from the research show that the highest percentage of removal obtained from the seed represents about 76% from the extract prepared with distilled water, which is due to the high polarity of the water that allows it to dissolve other substances, thanks to the difference in electronegativity between oxygen and hydrogen.